Maternal Outcome of Admitted Obstetric Patient in Intensive Care Unit of Dhaka Medical College Hospital, Bangladesh - Sarker, Subroto Kumar; Habibullah, Mohammad; Sardar, Mohammad Tanvir; Uddin, Md Kamal; Mohammad, Salim; Rahman, A K M Ferdous (Journal of Dhaka Medical College, 2025)
Background: The obstetric patient may suffer with any surgical/medical condition necessitating intensive care unit (ICU) admission. When admission ctiteria is fulfilled then early admission to Intensive Care Unit can reduce the maternal mortality. Aim: To observe the causes of Intensive Care Unit admissions, interventions, complications and maternal outcome. Materials and Methods: The study was a prospective longitudinal study conducted in the ICU of Dhaka medical college hospital Dhaka Bangladesh. The study period was 01/05/ 2019 to 30/04/2020. All the patient who had obstetric related complication were enrolled in this study. Data was collected from patient, patient’s attendants, patient’s clinical parameter and hospital documents (history sheet, investigation sheet and treatment sheet) and written in the pre-formed data sheet. The information obtained was type of admission, antenatal or postpartum, age, parity, obstetric status, primary diagnosis, associated medical and surgical condition, referral or inpatient shift to ICU, reason for ICU admission, mode of delivery, details of supportive interventions, complications. Results: The total admissions to the ICU were 272 obstetric patients. The mean maternal age was 24 ± 4. 2 years. Most of them were house wives (70%), daily laborers 10% and others contribute to 20%. Majority of the patients were multipara (68%). The more common indications of ICU admission were septic shock (26%) antepartum eclampsia (21.6%), hypovolemic shock (17%), post-partum eclampsia (8%), AKI following LUCS (8.8%), Peripartum cardiomyopathy (5. 8%).Highest number of patient (58.08%) come from obstetric ward and lowest number patient (4.41%) from medicine ward. 55.88 % patients required mechanical ventilation and mean duration of mechanical ventilation is 3 days. The duration of ICU stay varied from 2 -5 days in 191 cases ,6 to 10 days in 40 cases and more than 31days in 1 cases. Transfusion of Blood and blood products was needed in 66. 8% of patients and 11.39% patient required haemodialysis. 75 patient developed complications among those septicaemia (21 patient) was the highest, 11 patient AKI ,13 patient ARDS, 9 patient DIC and 4 patient pneumothorax. The survival rate is 61.01%. Conclusion: Septic shock was the major cause of ICU admission. About two third patients discharged alive. J Dhaka Med Coll. 2023; 32(2) : 124-130